Taman Rekreasi and Mini Zoo Kemaman interactive map / Shayyidatul Aslamiea Abdul Manaf - Abdul Manaf, Shayyidatul Aslamiea (2012)
Mini Zoo Kemaman is the largest zoo in the East Coast Malaysia. It is located at Kemaman ,Terengganu and operated by Majlis Perbandaran Kemaman(MPK). It was launched on 11 April 2009 by the Menteri Besar Terengganu, Datuk Ahmad Said opened to the public on the day after the 12 April 2009. The main objective of Mini Zoo Kemaman is to gain knowledge and create awareness and interest among students, residents and tourists to improve their responsibility to preserve and conserve the natural flora and fauna. The “Taman Rekreasi and Mini Zoo Kemaman Interactive Map” is developed to give an info motion about Mini Zoo Kemaman. The interactive map will ease the visitor to understand about animal in the zoo. The Mini Zoo Kemaman has an area of 35 acres. It also has many parts of places and animal that visitor could be visit. However, there is not provides proper guideline when visitor enter the zoo. From this situation, visitor will miss the interesting place in the mini zoo.In the zoo visitor can see many things, not just animal but they also have water theme park, suspension bridge, orchid garden, waterfall and more. It make difficult to explore the zoo entirely and miss lot of things. Visitor also cannot explore entirely whole of mini zoo.Visitor will get just some informaton and they will be miss some of information about mini zoo. This interactive map was developed based on ADDIE Model where it consists of Analysis, Design, Development, Implementation and Evaluation. The evaluation of this navigation map which focus on perceived usefulness, effectiveness and efficientness of the interactive map. This Mini Zoo Kemaman Navigation Map hopefully will help promotion of Mini Zoo Kemaman The result shows that the majority of the respondents are agreed that the “Taman Rekreasi and Mini Zoo Kemaman” is as guideline that can help visitor to visit Mini Zoo Kemaman. The result also show that the majority of the respondents agreed that the “Taman Rekreasi and Mini Zoo Kemaman” Courseware is easy to use, simple, and clear more than Mini Zoo Kemaman map